Hallazgo de un acueducto precolombino en la cuenca media del río Pacuare, Costa Rica - Hernández Alpízar, Ana Cristina (2013)
The activities necessary for the completion of the Environmental Impact Assessment for the Pacuare Hydroelectric Project revealed, through intensive archaeological surveys, extremely important Pre-Columbian evidence at the national level the find of the second settlement known in the country with hydraulic structures. The article is an adaptation from a segment in the archaeological section of the PH Pacuare (Hernández, A.C. and E., Ovares, 2005): Memoria Proyecto de Desarrollo Hidroeléctrico Pacuare, ICE, 2005.